Pengaruh Intensitas Penggunaan Kartu Plastik dan Mobile Payment terhadap Consumer Behavior: Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Islam - Agustin, Lismaini; Marliyah, Marliyah; Syarvina, Wahyu (Sci-tech Journal, 2023)
The purpose of this study was to determine the effect of the use of ATM cards and the use of mobile payments on consumer behavior in FEBI UINSU students. This study uses a quantitative approach. Data collection used a questionnaire with a simple random sampling technique of 98, but I rounded it up to 100 respondents. With an active student record of 2021 FEBI UINSU. The use of plastic cards and mobile payments contributes 89.4% to consumer behavior, the remaining 10.6% is explained by other variables outside this research model. The results of the t test concluded that the variable use of plastic cards and mobile payments had a positive and significant effect on consumer behavior (consumption behavior) in FEBI UINSU students. Based on the ANOVA test, the F-count was obtained at 411,118 which was greater than the F-table (3.09), it was concluded that the use of plastic cards and mobile payments had a simultaneous effect on consumer behavior (consumption behavior) of students at the Islamic Economics and Business Faculty of UIN Sumatra Utara. Keywords: Plastic Card, Mobile Payment, Consumer Behavior, Consumption Behavior, Intensity